The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0103-06631998000200015
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios craniomandibulares em pacientes edentados unilaterais inferiores com e sem próteses parciais removíveis (PPR): um estudo transversal utilizando o índice craniomandibular

Abstract: No presente trabalho, foi feito um estudo clínico em 102 pacientes, 78 mulheres e 24 homens, com idade variando entre 18 e 61 anos, com a finalidade de analisar comparativamente a severidade de sinais e sintomas das desordens craniomandibulares (DCM). Procedeu-se a anamnese, o exame clínico e as moldagens e estabeleceu-se um método de escores, através do qual se avaliou o grau de severidade das DCM. Os pacientes foram divididos em três grupos de 34 pessoas, assim constituídos: a) portadores de prótese parcial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In analyzing the craniomandibular index and its components, we observed mean values that were statistically higher in the group of patients with Rheumatoid Arthritis, who had more severe joint involvement when compared to the values attained from the disease-free patients; thus corroborating Gil and Nakamae' study 19 , in which they proved the safety of using the craniomandibular index when assessing craniomandibular signs and symptoms. Since the literature is not very abundant in references as to the use of such index, the values hereby attained could not be compared to those from other studies; we were only able to compare the large value differences among patients with (0.12) and those without Rheumatoid Arthritis (0.02).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In analyzing the craniomandibular index and its components, we observed mean values that were statistically higher in the group of patients with Rheumatoid Arthritis, who had more severe joint involvement when compared to the values attained from the disease-free patients; thus corroborating Gil and Nakamae' study 19 , in which they proved the safety of using the craniomandibular index when assessing craniomandibular signs and symptoms. Since the literature is not very abundant in references as to the use of such index, the values hereby attained could not be compared to those from other studies; we were only able to compare the large value differences among patients with (0.12) and those without Rheumatoid Arthritis (0.02).…”
Section: Discussionsupporting
confidence: 83%
“…Later studies showed that the use of these indexes allowed for a safe evaluation of the signs and symptoms of temporomandibular disorders in the patients investigated 18,19 .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Later studies showed that the use of these indices allowed for a safe evaluation of the signs and symptoms of temporomandibular disorders in the patients investigated. [29][30] So, in the current study, we used Helkimo index to measure the prevalence and severity of TMD among students. Some studies in nonpatient population indicate a high prevalence of TMD in both the general and nonpatient populations.…”
Section: Discussionmentioning
confidence: 99%
“…The study developed by Fricton and Schiffman 18 aimed at developing a craniomandibular index and test it as to its reliability. Later studies showed that the use of these indexes allowed for a safe evaluation of the signs and symptoms of temporomandibular disorders in the patients investigated 18 , 19 .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%